Making space for spatial talent. (December 2020) - Lakin, Joni M.; Wai, Jonathan
Spatial reasoning — the ability to mentally visualize, transform, and recognize symbolic information — is known to predict long-term success in many educational and occupational areas, including in STEM. Despite this, spatial reasoning measures are virtually absent in K-12 tests. Thus, such strengths are not prioritized in gifted identification and talent development. Joni Lakin and Jonathan Wai discuss why spatial reasoning matters for finding and developing talent, services schools might provide for students with these strengths, and how understanding spatial reasoning can help education leaders expand access to gifted education .